HONOR A QUIEN HONOR MERECE: DR. ENRIQUE NUÑEZ DE VILLAVICENCIO Y PALOMINO Dr. Enrique Nuñez de Villavicencio y Palomino a paradigm to be follow - Angela Rivero Suárez; Esther de la Caridad Díaz Vázquez (Universidad de Ciencias Médicas de La Habana, 2007)
El doctor Enrique Núñez de Villavicencio y Palomino (1872-1916) fue uno de los más ilustres profesionales en el campo de la Medicina y Cirugía, Tuvo un papel importante no solo en el desarrollo de las nuevas técnicas quirúrgicas, sino también como jefe de la Sanidad y Beneficencia de Cuba, tanto en la actividad civil como en la militar. El Dr. Núñez escribió muchos artículos relacionados con la Medicina, la Cirugía gineco-obstetra y modernizó el viejo Hospital Núm. 1 en el actual Calixto García, Esta revisión bibliográfica tiene como objetivo divulgar su vida y obra para que sirva como paradigma a los estudiantes de Medicina. Dr. Enrique Nuñez de Villavicencio y Palomino (1872-1916) was one of our the most outstanding professionals in the fields of medicine and surgery. He played an important role not only in the development of new surgical techniques, but also as a Secretary of Health care and Welfare of Cuba both in civil and military activities. Dr. Nuñez wrote many scientific articles related to Obstetrics, Gynecology and Surgery and he had also the great idea of turning the old and former Number One Hospital of Havana into the present Calixto Garcia Hospital . This bibliographic review has the purpose of divulging Enrique's life and work to as a paradigm to be follow by medicine students.